Pengaruh Financial Distress, Opini Audit, Dan Ukuran KAP Terhadap Auditor Switching - Holdi, Fio Prananda; Tarmizi, Rosmiati (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
The independence of an auditor is one of the main things for auditors, in order to maintain the level of auditor independence, the government issues regulations related to auditor rotation. This study plans to examine the impact of financial distress, audit opinion, and KAP size on auditor switching at consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) for the 2016 – 2020 period. The independent variables used are financial distress, audit opinion, and KAP size. and the dependent variable, namely auditor switching. The population in this study are consumer goods industrial companies as many as 37 companies. The examination technique used is logistic regression analysis using SPSS version 25 software. The results of this study are that financial difficulties do not have a significant impact on auditor turnover, while audit opinion and KAP size have a significant positive impact on auditor changes.